Land marketing management: analysis, inventory, accounting, reporting - Olijnyk, H.; Bielova А. (Ways to Improve Construction Efficiency, 2020)
The article considers the essence and features of state regulation of land sales in Ukraine, it substantiates the need for a preparatory process for this work. The tools offered in this work in the economic space of our country are tested at such important for Ukraine’s economy enterprises as Ukrtelecom and Ukrzaliznytsia, which have significant land resources, all technological processes of full range of works without which the sale of land is not advisable. It should be determined that land is real estate, which is taken into account on the balance sheet of the enterprise, is a business entity and is regulated by the requirements of applicable regulations, because the intangible assets of the enterprise are a very heterogeneous set. Therefore, users of financial statements, especially marketers, are interested in information about their composition to build an effective development strategy. It is concluded that for the formation of a marketing system of land management it is necessary to: determine and register the land plot (determine the property rights; analyze legal documents and accounting system; perform an inventory of both land and rights to it - rights to intangible asset). Authors conducted review and analysis of regulatory and legal support of the inventory procedure, as a part of an effective marketing inventory, which still remains an understudied procedure because, normatively, was not provided by regulations. A clear system of land inventory, registration, and timely analysis will reduce risks that cannot be completely eliminated. Paper concludes with the list of works on reconciliation of inventory results with data of technical passports issued by BTI, which should be the basis for the formation of the List of real estate and rights to them, and error prevention, which is the basis for the formation of an effective land management system.